Role of green financing and energy production to mitigate climate change in emerging economy like Bangladesh - Tanchangya, Tipon; Mia, Md Rakib; Roshid, Md Mustaqim; Chakma, Juni; Islam, Farvez; Rahman, Md Hasanur (International Journal of Sustainable Energy and Environmental Research, 2024)
This study examines the role of green financing and energy production to mitigate climate change in emerging economies like Bangladesh. In today’s world, climate change is a significant issue that impacts humans on an environmental, social, and economic level. However, this study aims to explain how to mitigate climate change with the support of green finance and green energy in Bangladesh. The study uses mixed methods to conduct the research, such as quantitative and qualitative methods. In this particular case, the study identified several crucial factors that contribute to the effects of climate change. Two environmentally friendly tools, like green finance and green energy, are used to fight climate change. Green finance, comprising financial instruments like green bonds and loans, finances significant investments in environmental projects, particularly renewable energy, that promote the transition to a greener, low-carbon economy and ultimately help to combat climate change. Solar, wind, hydropower, biomass, and biofuels are the common green energy production technologies in Bangladesh, which can play a pivotal role in reducing climate change by reducing greenhouse gas emissions. In Bangladesh, green finance contributes to investment in green energy projects, innovation in clean energy technologies, investment risk management, and energy transitions, according to the research. The study suggests valuable implications for the Bangladesh government, policymakers, and other policymakers taking effective initiatives to protect Bangladesh from the gulf of devastating climate change.